How age and L2 proficiency affectthe L2 lexicon. (February 2022) - Agustin-Llach, MariaPilar
Abstract: The present paper offers a study of the influence of age co-occurring with school grade and L2 proficiency on vocabulary production. Previous studies in classroom contexts confirmed that learners' lexical performance changes over time as their knowledge of L2 develops. Specifically, vocabulary becomes wider and more varied with time. In lexical availability studies, in particular, age, school grade, and L2 proficiency have been found to be significant variables. Here, we had 196 EFL learners of two different school grades (with corresponding ages and L2 proficiency levels) complete a lexical availability task: verbal fluency task to look into their vocabulary production and lexicon organization. Responses were analyzed against the framework of graph theory, together with descriptive tests. The results reveal that older learners produce more words, less frequent words, and words belonging to higher proficiency bands; differences between them and younger learners were very small, however. A more interesting result was brought to light by graph metrics, which reveal that learners in both groups used a category-ridden lexicon organization. Older learners display more single connections among peripheral words, giving rise to more disperse semantic networks approaching the structure found in native mental lexicons.